2022
DOI: 10.3390/pr10020259
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experiment (DoE) for Optimization of HPLC Conditions for the Simultaneous Fractionation of Seven α-Amylase/Trypsin Inhibitors from Wheat (Triticum aestivum L.)

Abstract: Wheat alpha-amylase/trypsin inhibitors remain a subject of interest considering the latest findings showing their implication in wheat-related non-celiac sensitivity (NCWS). Understanding their functions in such a disorder is still unclear and for further study, the need for pure ATI molecules is one of the limiting problems. In this work, a simplified approach based on the successive fractionation of ATI extracts by reverse phase and ion exchange chromatography was developed. ATIs were first extracted from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…This modified Osborne fractionation is time consuming and alternatives with lower number of extraction steps were established to extract all or the majority of proteins ( van den Broeck et al, 2009 ; Henrottin et al, 2019 ; Jira and Münch, 2019 ). Furthermore, specific protocols were developed to extract ATIs ( Geisslitz et al, 2018 ; Call et al, 2019 ; Sielaff et al, 2021 ; Sagu et al, 2022 ) using extractions solvents containing Ambic and/or NaCl with a pH between 7 and 8 and without any organic solvents and reducing reagents. We revealed that in our sample set, the Osborne fractionation and the TEP extraction resulted in comparable protein content by RP-HPLC-UV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This modified Osborne fractionation is time consuming and alternatives with lower number of extraction steps were established to extract all or the majority of proteins ( van den Broeck et al, 2009 ; Henrottin et al, 2019 ; Jira and Münch, 2019 ). Furthermore, specific protocols were developed to extract ATIs ( Geisslitz et al, 2018 ; Call et al, 2019 ; Sielaff et al, 2021 ; Sagu et al, 2022 ) using extractions solvents containing Ambic and/or NaCl with a pH between 7 and 8 and without any organic solvents and reducing reagents. We revealed that in our sample set, the Osborne fractionation and the TEP extraction resulted in comparable protein content by RP-HPLC-UV.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the sequences of the isoforms being studied may often not be unique, which limits its clear identification and thus, their assignment to proteins. Furthermore, theoretical mass of proteins listed by databases and those measured often differ strongly, e.g., as shown for CM3 (reference mass without signal 10.3389/fpls.2022.974881 peptide 15.8 kDa and measured mass 15.5 kDa) by several studies (Capocchi et al, 2013;Call et al, 2019;Sagu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%